2010
DOI: 10.1590/s0100-69912010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Fístulas orocutâneas após cirurgia de câncer da cavidade oral: fatores de risco

Abstract: O carcinoma de células escamosas é a neoplasia maligna mais frequente da cabeça e pescoço, e no Brasil o da cavidade bucal é o quinto mais freqüente em pacientes do sexo masculino (4,7%), e o sexto em pacientes do sexo feminino (2%), considerando todas as topografias da cabeça e pescoço 1 . A maioria dos pacientes apresenta doença avançada na primeira consulta, ou seja, tumores com está-dio clínico III ou IV em 53,4% dos casos, segundo estatísti-cas do Serviço de Registro Hospitalar de Câncer do Hospital Erast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The rate of postoperative complications was significantly lower compared with those reported by similar studies, as observed in a Brazilian retrospective study involving 159 patients, in which 47.3% of the sample had surgical site infection and 53.7% had suture dehiscence -values much higher than those found in the present study (6.1% for wound infection and 7.3% for suture dehiscence). This same study reported that microsurgical flaps would have a much lower risk of orocutaneous fistulae; however, due to the difficult access to microsurgery in our service, this type of flap was performed in only 4% of patients 16 .…”
Section: Discussionmentioning
confidence: 73%
“…The rate of postoperative complications was significantly lower compared with those reported by similar studies, as observed in a Brazilian retrospective study involving 159 patients, in which 47.3% of the sample had surgical site infection and 53.7% had suture dehiscence -values much higher than those found in the present study (6.1% for wound infection and 7.3% for suture dehiscence). This same study reported that microsurgical flaps would have a much lower risk of orocutaneous fistulae; however, due to the difficult access to microsurgery in our service, this type of flap was performed in only 4% of patients 16 .…”
Section: Discussionmentioning
confidence: 73%